PENGGUNAAN MEDIA MICRO CODING PLAY DALAM MENINGKATKAN DAYA INGAT ANAK USIA DINI KELOMPOK B DI RA TARBIYATUL HUDA - Yeni Irawati; Mukhtar Zaini Dahlan; Basuki Hadi Prayogo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on field research and analysis, the stimulation of children’s memory skills has not been optimally facilitated through learning media that are relevant, enjoyable, and aligned with their developmental stages. There is a need for learning innovations based on structured play; one potential alternative that remains rarely studied in Early Childhood Education settings is simple and concrete unplugged coding media. This study aims to analyze the effectiveness of implementing Micro Coding Play media in improving memory skills among Group B early childhood students at RA Tarbiyatul Huda. This research adopts a qualitative approach using the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, carried out in three stages: pre-action, Cycle I, and Cycle II. The research subjects consisted of 15 children — 10 boys and 5 girls. Memory assessment focused on three key indicators: (1) remembering simple instructions, (2) sequencing activity steps, and (3) imitating simple patterns using Micro Coding Play media. Data were collected through observation, documentation, and field notes, then analyzed using descriptive qualitative methods and presented by cycle. Classical success criteria were defined as met when at least 80% of the research subjects achieved the “Developing as Expected” or “Developing Very Well” categories. The results showed a significant improvement from Cycle I to Cycle II. Achievement for the indicator of remembering simple instructions increased from 20% to 80%, the ability to sequence activity steps rose from 20% to 93%, and the skill to imitate simple patterns improved from 27% to 93%. Based on these findings, it can be concluded that Micro Coding Play media is proven effective as an unplugged coding-based cognitive stimulation tool that suits the characteristics and learning styles of young children. Keywords: Memory, Early Childhood, Micro Coding Play